2017
DOI: 10.1186/s13256-017-1288-1
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum toxin-induced acute anterior uveitis in a patient with Behçet’s disease under infliximab treatment: a case report

Abstract: BackgroundInjections of lipopolysaccharide in animal models generate acute anterior uveitis (also known as endotoxin-induced uveitis), but the effects of lipopolysaccharide injection are unknown in humans. We describe an unusual case in which acute anterior uveitis was dramatically activated subsequent to botulinum toxin injection in a patient with Behçet’s disease but the acute anterior uveitis was satisfactorily attenuated by infliximab.Case presentationA 53-year-old Japanese man had normal ocular findings a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Only one longitudinal study reported bone volume changes induced by BoNT/A. The remaining reports were not related to joints and bones [9][10][11][12][13][14][15][16][17][18][19]. To our knowledge, we are reporting the first case of rheumatoid arthritis caused by BoNT/A.…”
Section: Prevalence and Presentationmentioning
confidence: 99%
“…Only one longitudinal study reported bone volume changes induced by BoNT/A. The remaining reports were not related to joints and bones [9][10][11][12][13][14][15][16][17][18][19]. To our knowledge, we are reporting the first case of rheumatoid arthritis caused by BoNT/A.…”
Section: Prevalence and Presentationmentioning
confidence: 99%
“…One case report described acute anterior uveitis activated subsequent to BT injection in a patient with Behçet's disease, which was attenuated by infliximab. 5 However, no ocular side effects have been described from the combination of BT injections and intravenous natalizumab. It is possible that the BT injection inducing the myasthenic syndrome also induced a bilateral anterior uveitis, left undiagnosed owing to the long delay between the decrease in vision and the first eye exam (1 month).…”
mentioning
confidence: 99%